Analysis of a clean hydrogen liquefaction plant integrated with a geothermal system. (10th January 2020) - Seyam, Shaimaa; Dincer, Ibrahim; Agelin-Chaab, Martin
Abstract: Hydrogen is attracting a lot of attention because of its high-energy content and lower weight and volume, making it a promising replacement of fossil fuels. Hydrogen liquefaction is an energy-intensive process that requires high electrical power. This paper presents a novel approach of a large-scale hydrogen liquefaction system combined with geothermal and isobutene power plant. The hydrogen liquefaction system uses a hydrogen Claude refrigeration system and a nitrogen precooling system to produce 335 ton/day of liquefied hydrogen. The mass flow rate of hydrogen in the refrigeration system and nitrogen precooling system were 14 kg/s and 52 kg/s, respectively, to produce specific energy consumption of 6.41 kWh/kg-LH2. The overall power consumption of the liquefaction system was 107 MW. This requires constructing three geothermal and isobutene power plants to produce 130 MW of electrical power. Some parametric studies were conducted to reduce the specific energy consumption (SEC). It is found that reducing the hydrogen mass flow rate to 9 kg/s and the high pressure to 20 bar results in the reduction of the SEC to 4.7 kWh/kg-LH2 . However, increasing the steam and isobutene mass flow and high pressure in the system results in an increase in the electric power delivered to 225 MW from 130 MW. Highlights: Hydrogen liquefaction process includes hydrogen Claude and nitrogen precooling cycles. The amount of liquefied hydrogen is 355 tpd and requires power consumption of 81.1 MW. The SEC, energy and exergy efficiencies are 6.47 kWh/kg-LH2, 19.8% and 63.7%, respectively. A water electrolyzer requires 18.5 MW to produce hydrogen gas. Geothermal and isobutene power plants are designed to provide 103 MW.